The Macroeconomics of Fertility in Small Open Economies: A Test of the Becker-Barro Model for the Netherlands and New Zealand - Poot, Jacques; Siegers, Jacques (School of Management Working Papers, 1998)
Becker and Barro (1988) formulated a theoretical model which identified a range of macroeconomic variables which can temporarily or permanently affect fertility in small open economies. While they suggested that their model provided a plausible explanation for the large shifts in fertility in western economies during this century, no formal econometric investigation was carried out. This paper tests the Becker-Barro model with relevant data which covers most of the 20th century for two small open economies, namely The Netherlands and New Zealand. The results show that government subsidies for having children have a strongly positive effect on fertility, while the provision of public pensions has a strongly negative effect. The degree of intergenerational altruism appears to have been declining. Moreover, there is some - albeit weak-support for the hypothesis that real interest rates positively influence fertility. The empirical analysis of the Dutch data is generally more conclusive than the analysis of the New Zealand data.